If you want to solve the equation -5 - (15 * y - 1) = 2 * (7 * y - 16) - y, you can calculate this using the following steps:
-5 - (15 * y - 1) = 2 * (7 * y - 16) - y
-5 - 15 * y + 1 = 14 * y - 32 - y
-5 + 1 + 32 = 14 * y - y + 15 * y
28 = 28 * y /28
y = 1
The result is 1.
288 is your answer
Hope this helps :) have a good day
Answer:
Yes you are right.........
Answer:
y = |x - 1|
Step-by-step explanation:
This graph is the standard graph of y = |x|, shifted 1 unit right. To shift 1 unit right, we have to replace x by x - 1. This works because it replaces f(1) with f(0), f(2) with f(1), etc., shifting the entire graph right.